Associations between gender, age and waist circumference - Stevens, J.; Katz, E.; Huxley, Rachel (Nature Publishing Group, 2010)
In December 2008, the World Health Organization (WHO) convened a consultation to discuss cut-points for waist circumference (WC). As part of that effort, this paper examines the impact of gender and age on WC. As WC is influenced by body weight, body composition and fat distribution, their associations with gender and age were reviewed. We also noted the relationships with sex hormones, parity and menopause. We then summarized data on gender, age and WC. This presentation is not intended to be comprehensive, but to provide an overview of the available research. There are large differences in body composition in men and women, with women having more body fat. Fat distribution also differs with gender, with men having a relatively more central distribution of fat. These differences begin early in life and become more apparent in puberty due to changes in sex hormone levels. In both, men and women, waist and waist-to-hip ratio increase with age. A large portion of this increase is driven by gains in body weight, but the increases observed are larger than those that would be predicted from increases in the body mass index alone, and increases in WC are seen with aging in the absence of weight gain. The current practice of using seperate waist cut-points by gender is appropriate. Although WC increases with age, so does the risk of many chronic diseases. An evaluation of the need for age-specific waist cut-points in adults would need to consider disease risk. © 2010 Macmillan Publishers Limited All rights reserved.